TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENIPUAN MELALUI SOSIAL MEDIA ONLINE MENURUT UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Rezki Mustika (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACTJudicial Review of Crime Against Fraud Through Online Social Media According to Law No. 11 Year 2008 on Information and electronic transactions, is the title chosen by the author as a requirement in order to obtain a degree Strata one (S1). The intent and purpose of the writing of this law is that the public is more aware of how the crime of fraud through eleltronik media in accordance with Article 378 of the Penal Code and Law No. 11 Year 2008 on Information and Electronic Transactions. Criminal fraud through online social media even this is not classified as nothing new considering the development of existing technology in an earlier era. The existence of consumer rights as a victim in accordance with Act No. 08 of 1999 on Consumer Protection should be because in this case it is not impossible that people can be victims of these crimes. In this case, the method used in this research is normative juridical, meaning that exposure which aims to obtain a picture (descriptive) about the state of the applicable law in a certain place and at a certain moment or concerning symptoms or events juridical Law and Juridical Sociological ie by research directly. In fact criminal fraud through online social media is often the case in the community, especially to the students / student because the student / student is user / user novice in the electronic activity. Utilization of information technology, media and communications have changed the behavior of human society and civilization globally. In connection with the development of Internet media, implementation of the Law on Information and Electronic Transactions in Samarinda that has begun to be applied to activities through electronic, some extension has been implemented by the government in order to make the public more aware and cautious interact in social media. The government has taken various dissemination to the public to be more vigilant in the use of the internet. Socialization in the form of dissemination of information broadcast by local television and private media, the distribution to the public, especially to the student / student. Society in general should also be careful before buying or selling so as not to impact on fraud. Sometimes a principal mode manifold in order to lure victims. As a wise consumer, the public should know in advance what you want to buy, the quality of goods, procedures for payment until the arrival of the goods into the hands of consumers. Law on Information and Electronic Transactions of this technology users should be vigilant and careful in using it. Because it can be, with a lack of caution can have a negative impact on the users themselves.